2021
DOI: 10.1186/s13578-021-00536-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1/ErbB4 signaling contributes to the anti-epileptic effects of the ketogenic diet

Abstract: Background The ketogenic diet (KD) has been recognized as a potentially effective therapy to treat neuropsychiatric diseases, including epilepsy. Previous studies have indicated that KD treatment elevates γ-Amino butyric acid (GABA) levels in both human and murine brains, which presumably contributes to the KD’s anti-seizure effects. However, this has not been systematically investigated at the synaptic level, and the underlying molecular mechanisms remain to be elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Western blotting was performed as described in our previous study [ 52 ]. In brief, brain tissue was homogenized in a RIPA Buffer containing (in mM): 50 Tris–HCl, pH 7.4, 150 NaCl, 2 EDTA, 1 PMSF, 50 sodium fluoride, 1 sodium vanadate, 1 DTT with 1% sodium deoxycholate, 1% SDS and 1% protease inhibitors cocktails.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described in our previous study [ 52 ]. In brief, brain tissue was homogenized in a RIPA Buffer containing (in mM): 50 Tris–HCl, pH 7.4, 150 NaCl, 2 EDTA, 1 PMSF, 50 sodium fluoride, 1 sodium vanadate, 1 DTT with 1% sodium deoxycholate, 1% SDS and 1% protease inhibitors cocktails.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of studies have reported that KD treatment elevated GABA levels in both human and animal brains, but it remains unclear whether changes in glutamate also occur [50][51][52]. GABAergic but not glutamatergic activity in the hippocampus was found to be enhanced by a KD in preclinical models of both acute and chronic seizures, and those changes were shown to be mediated by Nrg1/ErbB4 signaling [53]. Intriguingly, a long-term (i.e., 3 months) KD modified expression of the potassium chloride cotransporter 2 (KCC2), but not that of Na-K-Cl cotransporter 1 (NKCC1), in the dentate gyrus of rats [54], while 1 month of a KD was not effective at altering the expression of both transporters [55].…”
Section: Nervous Systemmentioning
confidence: 99%
“…It was recently demonstrated that d-3HB elicited its anti-epileptic effect through activation of K ATP channels and GABA B signaling, which led to reduced neuronal firing (Li et al 2017). Recent studies have revealed novel signaling pathways by which d-3HB may be involved (Wang et al 2021), as well as its potential for treating other forms of epilepsy (Brunner et al 2021).…”
Section: D-3hb and Brain Healthmentioning
confidence: 99%